(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study addresses the demographic transformations that Iraq has undergone since 2003 and their profound impact on the country’s social, economic, and political structures. Following the U.S. occupation, Iraq experienced significant changes in its population structure due to migration, displacement, high population growth rates, and an increasing proportion of youth. These transformations were accompanied by various challenges, including unemployment, the spread of informal housing (slums), the deterioration of education and healthcare systems, and the weakening of family structures. Additionally, these changes contributed to the destabilization of social security and the rise of sectarian conflicts. The research explores the concept of demographic transformation, the underlying causes of these changes in Iraq, and their impact on social values, family structures, and the labor market. It also examines key indicators of this transformation, such as population pressure, migration, unemployment, and declining fertility rates. The study concludes that Iraq is currently undergoing a critical phase that could potentially allow it to benefit from a “demographic dividend” — provided that balanced population policies are implemented, infrastructure is improved, migration is managed effectively, and the role of demographic and social research institutions is strengthened.